(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2006)
Absorbed IR spectrums of vitamin E in presence of dimethyl-, diethylsulphoxides in CCl4 have been investigated. It has been shown that complex-formation of vitamin E with sulphoxides is the result of formation of hydrogen bond between hydrogen of vitamin E hydroxyl group and oxygen of the sulphoxides S=0 group. It have been established the equilibrium constants (K) of vitamin E complexes with dimethylsulphoxide (K=13.2 L/mol) and diethylsulphoxide (K=18.2 L/mol) at 23℃.